DEVELOPING SEMANTIC ONTOLOGY FOR PRACTICAL DIGITAL BALINESE DICTIONARY - Pramartha, Cokorda; Arka, I Wayan; Kuan, Kevin KY; Darmawan, IDMBA (Proceeding International Conference on Information Technology, Multimedia, Architecture, Design, and E-Business, 2022)
There has been an increase in the number of young millennial Balinese who are bilinguals showing a shift with high competency in Indonesian at the concomitant expense of their Balinese language competency and related indigenous knowledge. The project takes advantage of the momentum with the surge of the enthusiasm and needs for online learning in the current context of COVID-19. The project focuses on digital dictionary research and development, addressing a clear gap in this space of Balinese digital humanity to have a learning resource in the broader literacy context of culture and language preservation and education. The digital dictionary online design is expected to benefit Balinese learners and other parties, including academic communities in Bali and across the globe. The language digital dictionary is a cross-lingual system to facilitate the translation of a source language to a target language based on keywords to query the translation. The use of keyword-based query for translation presents an ambiguity, which the use of ontology can help to minimise. The design, development, and evaluation of Balinese language dictionary ontology in this study was done in consultation with Balinese language experts.